Kinetics and mechanism of sol-gel transformation between some trivalent- and tetravalent-metal ions and Sodium alginate Anionic polyelectrolyte with formation of coordination Biopolymeric structure polymembranes Hydrogels of Capillary Structures Ex (JOURNAL OF ADVANCES IN CHEMISTRY, 2007)
Abstract          The kinetics of sol-gel transformation between A13+, La 3+ and Th4+ metal ion electrolytes and sodium alginate sol have been studied complexometrically at various  temperatures. In the presence of a large excess of sodium alginate sol concentration over that of metal ion electrolyte, the pseudo first–order plots of exchange showed sigmoidal curves with two distinct stages. The initial part was relatively fast and curved significantly at early times, followed by a slow decrease in the rates of exchange over longer time periods. The rate constants of gelation showed second-order overall kinetics which was first order in the concentration of both reactants. The thermodynamic parameters have been evaluated and tentative gelation mechanisms consistent with the kinetic results of gelation are suggested. The stability of these ionotropic metal-alginate complexes has been discussed in terms of the coordination geometry and strength of chelated bonds.